Musculoskeletal Modeling of the Compensatory Role of the Shoulder Muscles in Ensuring the Stability of the Shoulder Joint in the Conditions of Partial Traumatic Tear of the Supraspinatus Muscle Caused by Calcific Tendinitis - Lazarev, I.A.; Biliavskyi, V.O.; Yuriichuk, L.M.; Bohdan, S.V. (TERRA ORTHOPAEDICA, 2023)
Relevance. The presence of calcium deposits in the rotator cuff tendons usually leads to a restriction of the biomechanics of the shoulder joint and, in particular, to a failure of the scapulohumeral rhythm. The question of the compensatory participation of the muscles of the shoulder girdle in ensuring the stability of the shoulder joint in conditions of partial-thickness damage to the tendon of the supraspinatus muscle caused by calcific tendinitis remains interesting and understudied. Objective: to carry out skeletal and muscular modeling with the study of the compensatory participation of the rotator cuff muscles in ensuring the stability of the shoulder joint during the elementary movement of elevation of the upper limb in conditions of partial-thickness damage to the supraspinatus tendon caused by the presence of calcification in it. Materials and Methods. For the analysis we used simulation modeling in the software package AnyBody Modeling System™ (AnyBody Technology A / S, Denmark) for Windows. The calculation was carried out using the software component Mannequin, selected from the AnyBody Managed Model Repository™ model collection. The parameters of joint forces acting in the direction of three axes – X, Y, Z – were calculated, where the X axis corresponded to the anterior-posterior force direction (antero-posterior force), the Y axis – to the inferior-superior force direction, the Z axis – compression-distraction force direction (medio-lateral force) on the shoulder joint. The object of the study was muscle activity (Activity) and muscle strength (Fm) of m. deltiodus clavicular, m. deltiodus scapularis, m. infrapsinatus, m. subscapularis, m. teres major, and m. teres minor while simulating a decrease in the strength of m. supraspinatus by 50% caused by the presence of calcification in the thickness of its tendon. Results. With complex movement of the upper limb, associated with the elevation of the upper limb, in conditions of partial-thickness tear to the m. supraspinatus, with a decrease in its strength by 50%, there is a compensatory increase in the strength of the muscles of the shoulder joint – the posterior portion of the m. deltoidus scapularis, m. infraspinatus and m. subscapularis, to ensure the stability of the shoulder joint. Taking into account minor changes in joint reactions along three axes, with a decrease in the strength of m. supraspinatus caused by the presence of calcification in its thickness, the compensatory mechanism of including additional muscle activity and muscle efforts of other muscles of the shoulder girdle provides the necessary stability of the shoulder joint in these conditions. Conclusions. The study confirms the possibility of successful application of programs of conservative treatment of calcifications of the m. supraspinatus tendon, aimed at developing the compensatory capabilities of the muscles of the shoulder girdle.